Virtual reality contents based on X3D and HTML5 Canvas. (18th April 2014) - Yang, Dongxu; Yun, Yoemun; Cha, Si–Ho
Virtual reality 3D web technology can combine with HTML5 technologies and X3D contents to achieve real–time display without plug–in. X3D strives to become the 3D standard for the web as integrated in the HTML5 standard. HTML5 is able to support X3D format to achieve 3D virtual reality on the web. Blender software can create 3D models and export them to X3D files. X3D files are displayed in real time on web browsers that support HTML5. The X3D files created with Blender software give users excellent 3D real–time interactive operation experience. Therefore, this paper introduces how to achieve 3D virtual reality contents on the web by using X3D files and HTML5 canvas.